2022
DOI: 10.3390/fire5050141
|View full text |Cite
|
Sign up to set email alerts
|

Fire Regime Analysis in Lebanon (2001–2020): Combining Remote Sensing Data in a Scarcely Documented Area

Abstract: Fire is a recurrent disturbance in Mediterranean ecosystems. Data assemblage from forest fire services can provide useful information for understanding climate controls on daily fire hazard or long term trends. Located at the driest range of the Mediterranean bioclimate, and with contrasting socio-political systems compared to the European area, the southern Mediterranean ecosystems are subjected to more extreme climate and social events. This could potentially lead to unique fire regimes and trends worth bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 98 publications
2
7
0
Order By: Relevance
“…In turn, the wildfire size distribution in the database should reflect as closely as possible the actual wildfire distribution: most of the wildfires are small, few are large, and large wildfires account for the most damage and area burned [61,68]. We found that 10 ha was the minimal burned area that we could detect using multiple independent approaches (both field-based and remotely sensed), and which at the same time corresponded to the actual wildfire size distribution in Israel, which is similar to the size (6.3 ha) found in Lebanon (Israel's neighboring country to the north, which has a similar climate [45]). We stress that the choice of minimal burned area threshold is not straightforward and reflects a tradeoff between detectability and outcome.…”
Section: Incomplete Records Of Wildfire Events Spatial and Temporal I...mentioning
confidence: 53%
See 3 more Smart Citations
“…In turn, the wildfire size distribution in the database should reflect as closely as possible the actual wildfire distribution: most of the wildfires are small, few are large, and large wildfires account for the most damage and area burned [61,68]. We found that 10 ha was the minimal burned area that we could detect using multiple independent approaches (both field-based and remotely sensed), and which at the same time corresponded to the actual wildfire size distribution in Israel, which is similar to the size (6.3 ha) found in Lebanon (Israel's neighboring country to the north, which has a similar climate [45]). We stress that the choice of minimal burned area threshold is not straightforward and reflects a tradeoff between detectability and outcome.…”
Section: Incomplete Records Of Wildfire Events Spatial and Temporal I...mentioning
confidence: 53%
“…Unfortunately, global fire datasets are not relevant for regions where most fires are small and have a short duration, as they go undetected by NASA's active fire products [33,45]. Taking Israel as an example, the global fire atlas [14] for the years 2015 and 2016 had only 37 and 38 wildfires, with a median area of 21 and 42 ha and a total burned area of 1759 and 2981 ha, respectively.…”
Section: Wildfire Database Creation From Remote Sensing and Field Datamentioning
confidence: 99%
See 2 more Smart Citations
“…These fires may seriously degrade forest habitats in this country, a large part of which may not be restored [9]. However, accurate and spatially explicit BA data about this region, as in several middle-eastern and north-African countries, are scarce or even lacking [10].…”
Section: Introductionmentioning
confidence: 99%